Impact of Activation Energy and Temperature-Dependent Heat Source/Sink on Maxwell–Sutterby Fluid. (4th August 2020) - Sajid, T.; Tanveer, S.; Sabir, Z.; Guirao, J. L. G.
Abstract : The present article aims to investigate the behaviour of Maxwell–Sutterby fluid past an inclined stretching sheet accompanied with variable thermal conductivity, exponential heat source/sink, magneto-hydrodynamics (MHD), and activation energy. By utilizing the compatible similarity transformations, the nondimensionless PDEs are converted into dimensionless ODEs and further these ODEs are tackled with the help of the bvp4c numerical technique. To check the legitimacy of upcoming results and reliability of the applied bvp4c numerical scheme, a comparison with existing literature and nonlinear shooting method is made. The numerical outcomes delivered here show that the temperature profile escalates due to an augmentation in the heat sink parameter and moreover mass fraction field escalates on account of an improvement in the activation energy parameter.